Eternal Returns to a Peak Experience: Creating and Curating Play(ful) Tributes to Twin Peaks - Heljakka Katriina (Finland, 2022)
This article documents the infinite allure of the cult series according to its own logic: In the spirit of play, what follows is a creative reflection of the author’s personal exploration of Twin Peaks through fandom, artistry and curatorship that sets to traverse the boundaries of a traditional academic text. The autoethnographic, artistic compilation includes a retrospective and reflective documentation of the author’s past experiences, exhibitions and events in relation to the Twin Peaks television series, seasons 1, 2 and 3; Twin Peaks: The Return, featuring a written introduction as well as ample visual and audiovisual material from the Peak Experience art exhibitions and related adventures. In the article, connections between the fictional series, its imaginative characters, and the actual geographic space of the pilot’s (Season 1) filming locations are made to fan-art, as they are discussed as inspirational resources for fans and artists in the creation, crafting and curation of play(ful) tributes to Twin Peaks. As a scholarly contribution of a researcher of toys and play, the text references contemporary sources on play theory as well as source texts tying the reflection with analyses of Lynch’s oeuvre. The discussion flows freely between the opus maximus that Twin Peaks is, and the innate playfulness and toyness of the artistic pieces produced for the ongoing exhibition series, as well as the author’s own photoplay in reference to the activities as a fan of the television series. The collage of photographic and audiovisual ‘playworks’ and artworks, which function as research material for the analysis, are claimed to follow a ‘lynchian aesthetic’—multiple and ambiguous in their identity – as proposed by FosterWallace (1997, 151), and represent the results of creation and curation of play(ful) tributes to Twin Peaks. By asking how ‘the happening again’ manifests in a loop of eternal returns, the author highlights the timeless gold of Twin Peaks as a source for artistry, fandom and play of creative adults.